FAKTOR – FAKTOR YANG MEMPENGARUHI KEPERCAYAAN DIRI ANAK TAMATAN RA DI SD KELAS 1 KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Dewi, Vidra Yulanda; Risma, Devi; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is to determine the factors the factors wich influence the self-confidence of graduates from RA in 1 graders elementary school District of Pujud, Rokan Hilir Regency. The populations of RA graduates in 1 graders of elementary school District of Pujud, Rokan Hilir District are 30 people, the subject of this research are 30 people. The type of this research is quantitative descriptive wich then to test the validity the qualitative method is used. Data collection techniques through observation and interview. Data analysis technique is the percentage formula. After getting the results of percentage, the research do interview repeatedly in order to investigate more in factors wich are impact to the self-confidence. The interview session has done with parents, siblings, teachers, friends, people and children. As we know that the external factors that influence the self-confident in children are parents, teachers, friends, people and experience. On the other hand the internal factors are personal skill, personal achievement, ambition and strong dedication.Keywords: Self-Confidence